The Effect of Competitive Strategy and Innovation on Performance - Asrianto Nasir; Syamsu Alam; Andi Aswan (Hasanuddin Journal of Business Strategy, 2021)
This study aims to analyze the linking of the competitive strategy on the operational unit performance through the innovation at PT. Semen Tonasa. The data collected using a survey method using the Google Form application and distributed to 117 employees of operational unit heads at PT Semen Tonasa consisting of echelon 3 and 4 employees. The data were then analyzed using the Structural Equation Model (SEM) with the IBM SPSS AMOS application version 22. On the basis of the findings, the study indicated that the competitive strategy and innovation significantly and positively affect the performance. The relationship between the competitive strategy and the innovation also showing a significant and positive relationship.